Analysis of Yogyakarta Special Fund on Community Welfare Case Study of Gunungkidul Regency - Rahman, Ilyasin Aditya; Sodik, Jamzani; Nurlitasari, Arini (International Journal of Scientific Research and Management (IJSRM), 2024)
Special Fund (Danais) is a special source of funding intended for development and development in the Special Region of Yogyakarta. This study aims to determine the effect of the Yogyakarta Special Fund on the Welfare of the People of Gunungkidul in 2023. This privilege fund is given to DIY as part of the privileges stipulated in the Constitution of the Republic of Indonesia Year 1945 Article 18B Paragraph 2. The state of art in this study is to determine the benefits and effects of development activities related to special funds so that an in-depth study is needed so that changes in community welfare in Gunungkidul Regency can be known. The problem in this study is the effect of the Yogyakarta special fund on the welfare of the people in Gunungkidul Regency and its impact before and after receiving the special fund. Data used primary data through survey results and literature reviews. Mmethod used Specialty Program Effectiveness Analysis. The results of this study value the effectiveness of IKM 81,968 which shows a high level of satisfaction. Meanwhile, in other tests, in general, they felt the positive impact of implementing good programs for community groups. Meanwhile, based on the results of different tests, the four fields tend to experience an increase in welfare after getting special funds in Gunungkidul Regency.